Hydrothermal synthesis of layered molybdenum sulfide/N-doped graphene hybrid with enhanced supercapacitor performance. (April 2016) - Xie, Bingqiao; Chen, Ying; Yu, Mengying; Sun, Tu; Lu, Luhua; Xie, Ting; Zhang, Yong; Wu, Yucheng
Abstract: Graphene-based composites have been deemed as promising materials in renewable energy-storage applications. Herein, we report a hybrid architecture consisting of layered molybdenum sulfide nanosheets/N-doped graphene (MoS2 /NG) synthesized by one-pot hydrothermal method. By adjusting precursor ratios, flower-like MoS2 /NG hybrid with nitrogen content of 3.5 at.% on the graphene layers can be obtained. Electrochemical characterizations indicate that the maximum specific capacitance of the MoS2 /NG electrodes reaches up to 245F/g at 0.25A/g (and 146F/g at 20A/g). In addition, the electrode exhibits superior cyclic stability with 91.3% capacitance retention after 1000 cycles at 2A/g. The outstanding performance of the MoS2 /NG hybrid benefits from the synergistic effect between the layered MoS2 and N-doped graphene.